A Study on Factors Contributing to Stress among Working Women in Kanniyakumari District (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the multifaceted factors contributing to stress among working women. With the growing participation of women in the workforce, understanding the unique stressors they face is crucial for promoting their well-being. Through a comprehensive literature review and empirical analysis, this research examines various elements such as workload, role conflict, job insecurity, and personal life issues that contribute to stress levels among working women. By identifying and analysing these factors, the study aims to provide valuable insights for organizations and policymakers to develop targeted interventions and support systems to mitigate stress and foster a healthier work environment for women. This study examines the factors contributing to stress among working women. The research aims to understand the various elements such as workload, role conflict, job insecurity, and personal life issues that influence stress levels in this demographic. By conducting a thorough literature review and empirical analysis, the study seeks to identify key stressors and their impact on working women. The findings are expected to provide valuable insights for organizations and policymakers to develop targeted interventions and support systems to address these stress factors effectively, ultimately promoting a healthier work environment for women.